The Johnstown flood - Huddleston, Emma (Engineering disasters (Core Library (Firm)), 2020)
Explores the historical disaster of the South Fork Dam's breaking and subsequent Johnstown flood in Pennsylvania in 1889. Discusses the engineering mistakes that contributed to the dam's failure and how it changed the way dams are built today. Includes a glossary.